Enhancing Disaster Preparedness Skills through Mitigation Education in Group B Early Childhood Education - Wulan Suci Eka Handayani; Fitriana Fitriana; Sita Awalunisa; Andi Agusniatih (Universitas Negeri Semarang, 2025)
Disaster preparedness has not been optimally integrated into early childhood education, resulting in limited preparedness skills among children in disaster-prone areas. Although disaster mitigation education has been widely promoted, empirical evidence regarding its implementation at the early childhood level remains limited. This study aimed to improve disaster preparedness skills through mitigation education in Group B of an early childhood education institution in a flood-prone area. This research employed a classroom action research design based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 15 children, and the intervention was carried out over six learning sessions. Data were collected through observation, interviews, and field notes, and analyzed using a combination of qualitative and quantitative approaches. The results showed a consistent improvement in children's disaster preparedness skills, with the average score increasing from 5.27 in the pre-cycle to 7.73 in Cycle I and 10.13 in Cycle II, out of a maximum score of 12. These findings indicate that mitigation education is effective in enhancing disaster preparedness skills among early childhood learners. It is recommended that disaster mitigation education be systematically integrated into early childhood learning to foster awareness and preparedness from an early age, particularly in disaster-prone environments.